Thermo-mecano-metallurgical modelling of welding: application to welded joints in nuclear power plants - Cosimo, Alejandro (2014)
Fil: Cosimo, Alejandro. Universidad Nacional del Litoral. Facultad de Ingeniería y Ciencias Hídricas; Argentina.